Research trends in library and information science in Philippine universities - Reji Chandra, D. T.; Vallejo, Rosa M.; Picache, Ursula G. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1981)
This study is about the research trends in Library and Information Science in the Philippine universities offering graduate studies in the field. One hundred and fifty nine theses and special problems done in the six universities in the Philippines were studied to collect data. The six universities are Philippine Normal College, Philippine Women's University, University of San Carlos, University of Santo Tomas, University of the East, and University of the Philippines.
The study aimed to answer questions related to research like: area of research; methodology employed; change of trend; logical importance; generalization; and relationships between factors such as sex of the researchers and educational background to area and method.
The study revealed that bibliographic aids and tools were chosen for research mostly; the survey method is predominantly employed in conducting research; there is an increase of bibliographic aids and tools in recent years; only a few studies used logical relations and generalizations; female researchers choose to compile more bibliographies and indexes than the male researchers.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Information science -- Research -- Philippines; Library science -- Research -- Philippines